Derecho a la propia imagen y convicciones religiosas en el trabajo: distintivos religiosos - Salido, Mercedes (Trabajo y Derecho, 2023)
The right to the own image of the subjects that operate in the bosom of an employment relationship is reinforced and acquires a special interest when it's fruit of their religious conviction, given the growing plural religious profile of the intervening parties. In this study, what is, probably, the most problematic assumption is analyzed: the use of clothing and other religious badges at the time of contracting, development and termination of the employment contract. In short, the need is verified, for its adequate guarantee, of a positive and reasonable action on the part of the business board in the organization of the work center, in proportion to the interests in conflict, thus defending a benefit aspect in its exercise.
Right to the own image and religious convictions at work: religious distinctive
Keywords: image; labor; religious freedom; right; symbols; Scopus